2015
DOI: 10.1245/s10434-015-4528-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Postmastectomy Radiotherapy and Survival Rates for Breast Cancer Patients with T1–T2 and One to Three Positive Lymph Nodes

Abstract: The effectiveness of radiotherapy depends on the combination comprising the number of positive lymph nodes and tumor size, which may enable more precise patient selection for PMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
1
44
2
Order By: Relevance
“…30 recommendations continue to support the consideration of post-mastectomy radiation for 1-3 lymph node positive patients despite a SEER data study evaluating patients from 1998 to 2008 that found no survival benefit in patients post-mastectomy who received radiation for 1 positive lymph node. [30][31][32][33][34] Since the vast majority of patients for whom IBR is offered are early stage and clinically node negative, those who are found to be pathologically node positive are typically in the 1-3 node positive category, and the benefits of radiation to these patients should outweigh the potential toxicity and the implications for successful reconstruction. 31 Discussions around possible post-mastectomy radiation avoidance in IBR patients fits with an evolving trend to choose wisely with adjuvant treatments such as radiation in patients aged 65 years or older, where radiation (at least in breast conserving surgery for early stage disease) can be safely avoided without adversely impacting overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…30 recommendations continue to support the consideration of post-mastectomy radiation for 1-3 lymph node positive patients despite a SEER data study evaluating patients from 1998 to 2008 that found no survival benefit in patients post-mastectomy who received radiation for 1 positive lymph node. [30][31][32][33][34] Since the vast majority of patients for whom IBR is offered are early stage and clinically node negative, those who are found to be pathologically node positive are typically in the 1-3 node positive category, and the benefits of radiation to these patients should outweigh the potential toxicity and the implications for successful reconstruction. 31 Discussions around possible post-mastectomy radiation avoidance in IBR patients fits with an evolving trend to choose wisely with adjuvant treatments such as radiation in patients aged 65 years or older, where radiation (at least in breast conserving surgery for early stage disease) can be safely avoided without adversely impacting overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate results from a combined analysis of patients who had breast cancer with 1 to 3 positive lymph nodes from the Surveillance, Epidemiology, and End Results program and the NCDB who underwent mastectomy between 1998 and 2008, in which the reported rate of PMRT use was similar (21.5%) to that reported in our current study (22.5%). 12 However, in that analysis, the dose range for PMRT was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of consistency in identifying these subsets in the era of modern surgical and systemic therapies has likely resulted in highly variable treatment patterns across the United States. Reports from national and state cancer registries have demonstrated that PMRT rates vary from 21% to 36% in these patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCDB is a comprehensive national oncologic database with detailed information available regarding sociodemographic, tumor, and treatment characteristics . Several comparison studies have documented the validity of NCDB‐based analysis . However, the current study has several limitations.…”
Section: Discussionmentioning
confidence: 94%